Larvicidal Impact of Some Local Medicinal Plant Extracts Against Aedes Aegypti (L.) - Sharower, MG; Latif, MA (Journal of the Asiatic Society of Bangladesh, Science, 2018)
The larvicidal potential of different solvent (hexane, chloroform, ethyl acetate, acetone and methanol) crude leaf extracts of five plants (Blepharis maderaspatensis, Elaeagnus indica, Maesa indica, Phyllanthus wightianus and Memecylon edule) were tested against the fourth-instar larvae of Aedes aegypti. All the tested extracts showed moderate to good larvicidal activities. However, the maximum larval mortality was detected in acetone extract of E. indica (LC50 90.89, LC90 217.21 and LC99 441.88 ppm) followed by M. indica acetone extract (LC50 173.21, LC90 289.86 and LC99 441.04 ppm). The results revealed that larvicidal properties of the four selected plants and encourages further investigation for the bioactive compounds that might possess good larvicidal properties in pure form. Asiat. Soc. Bangladesh, Sci. 44(1): 61-67, June 2018